Immunogenicity and reactogenicity of repeated intradermal mRNA COVID-19 vaccines administered as a second booster dose in a Thai geriatric population - Assantachai, Prasert; Niyomnaitham, Suvimol; Toh, Zheng Quan; Thammasalee, Monthira; Pengsorn, Napaporn; Monklang, Wiyachatr; Licciardi, Paul V.; Chokephaibulkit, Kulkanya (Frontiers in Immunology, 2024)
Background: Geriatric populations are at an increased risk of severe presentations, hospitalization, and loss of life from COVID-19. Few studies have explored vaccination regimens in adults >65 years old. Repeated booster vaccination is required for high-risk populations as COVID-19 vaccine efficacy is short-lived. We compared the immunogenicity and reactogenicity of second intradermal (ID) COVID-19 booster vaccination with second intramuscular (IM) vaccination in older adults. Methods: This single-center, open-labelled, prospective, cohort study conducted at Siriraj Hospital enrolled older adults ≥65-year-old who previously received a first booster (third dose) mRNA vaccine (mRNA-1273 or BNT162b2) via ID or IM administration. Participants were allocated to receive a second booster of the same vaccine type and route as their first booster 16-17 weeks thereafter. Anti-SARS-CoV-2 receptor binding domain IgG and neutralizing antibody titers against Wuhan and Omicron subvariants (BA.1, BA.2, and BA.4/5) were measured 2 weeks after vaccination. Results: Of 91 enrolled participants, 72.5% were female, with a median age of 75 years. Forty-nine participants (53.8%) received a second ID booster, and 42 (46.2%) a second IM booster. Two weeks after the second booster, all groups generated anamnestic IgG antibody responses that were 5.41-10.00-fold higher than at baseline. Overall, higher antibody GMTs against Wuhan and Omicron subvariants were observed in IM compared with ID regimens. ID mRNA-1273 induced similar GMTs as IM BNT162b2 2 weeks after the second booster against Wuhan (486.77 [321.48, 737.05] vs 472.63 [291.24, 767.01], respectively; p = 0.072). Higher GMTs against Omicron BA.1 (GMR [95% CI], 1.71 [1.39, 2.11]; p = 0.023), BA.2 (1.34 [1.11, 1.62]; p = 0.845), and BA.4/5 (1.10 [0.92, 1.33]; p = 0.531) were seen in all groups at 2 weeks after the second booster compared with 2-4 weeks after the first booster. Both local and systemic AEs were less frequent after the second than the first booster, regardless of administrative route and vaccine type. Local AEs were significantly more frequent in ID mRNA-1273 arms than their respective BNT162b2 arms 2 weeks after the second booster (ID-mRNA-1273 vs ID-BNT162b2: p ≤ 0.001). Conclusion: Repeated fractional ID vaccination may be an alternative booster vaccination strategy for geriatric populations.